2018
DOI: 10.1257/pol.20150066
|View full text |Cite
|
Sign up to set email alerts
|

Cheating and Incentives: Learning from a Policy Experiment

Abstract: We use a database generated by a policy intervention that incentivized learning as measured by standardized exams to investigate empirically the relationship between cheating by students and cash incentives to students and teachers. We adapt methods from the education measurement literature to calculate the extent of cheating and show that cheating is more prevalent under treatments that provide monetary incentives to students (versus no incentives or incentives only to teachers). We provide evidence suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…In the developing world, corruption and cheating are quite prevalent; numerous dictators (e.g., Suharto, Marcos, and Duvalier) have shamelessly looted their countries, which have suffered greatly after the fall of the dictatorship; such corruption hinders investment and growth. In addition, recent experimental evidence has demonstrated that setting goals (Schweitzer, Ordóñez and Douma, 2004;Cadsby, Song and Tapon, 2010) or using policies such as team incentives (Conrads et al, 2013), random bonuses (Gill, Prowse and Vlassopoulos, 2013), or performance-based bonuses (Jacob and Levitt, 2003;Martinelli et al, 2018) can exacerbate cheating behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In the developing world, corruption and cheating are quite prevalent; numerous dictators (e.g., Suharto, Marcos, and Duvalier) have shamelessly looted their countries, which have suffered greatly after the fall of the dictatorship; such corruption hinders investment and growth. In addition, recent experimental evidence has demonstrated that setting goals (Schweitzer, Ordóñez and Douma, 2004;Cadsby, Song and Tapon, 2010) or using policies such as team incentives (Conrads et al, 2013), random bonuses (Gill, Prowse and Vlassopoulos, 2013), or performance-based bonuses (Jacob and Levitt, 2003;Martinelli et al, 2018) can exacerbate cheating behavior.…”
Section: Introductionmentioning
confidence: 99%
“…There are also priming effects found, in that cheating drops when participants pay attention to the private environment instead of the business environment (Cohn et al, 2014). Moreover, cheating is stronger if it comes with higher incentives (Martinelli et al, 2018) and if people try to avoid losses (Grolleau et al, 2016). We acknowledge that these are strong determinants, but they do not play a role in our approach: our design purposely neither has implications for other persons, nor framing effects or potential losses.…”
Section: Introductionmentioning
confidence: 96%
“…See, e.g.,Akerlof and Kranton (2000); Tirole (2009, 2011); Bénabou, Ticchi, and Vindigni(2015); Bénabou, Falk, and Tirole (2018); Benjamin et al (2012); Benjamin, Choi, and Fisher (2016); Bursztyn et al (2015); Kuziemko et al (2015).7 Among studies of preferences for truthfulness and economic incentives, see, e.g.,Gibson, Tanner, and Wagner (2013) andGneezy (2005) Jacob and Levitt (2003). andMartinelli et al (2018) show that monetary rewards induce teachers and students to cheat on tests.…”
mentioning
confidence: 99%